Lignocellulose biorefinery engineering : principles and applications - Chen, Hongzhang (Woodhead Publishing in energy, 2015)
Biomass resources and their refining are key research topics internationally as alternatives to fossil fuel resources and oil refining. This book explores the heterogeneous nature of lignocellulosic biomass, which restricts its use as a raw material, and describes the theoretical basis of the lignocellulose refinery. It puts forward the theory of the integrated biomass refinery system, which produces multiple products, including biofuels, biomaterials, biochemicals, food and feed based on careful fractionation of the raw material. Chapter 1 introduces the significance and development of ligno.